Indigenous ecological knowledge (IEK) of the Osing tribe in Kemiren village as a teaching material - M. Mistianah; Diyah Ayu Widyaningrum; Ismi Nurul Qomariyah; Dwi Budiono (Research and Development in Education (RaDEn), 2024)
The lack of integration of Indigenous Ecological Knowledge (IEK) into formal education hinders the preservation and transmission of valuable environmental and cultural practices. The purpose of this study was to develop biology teaching materials that incorporate the Indigenous Ecological Knowledge of the Osing tribe, especially for high school students in Kemiren village, Bayuwangi regency. This study used a Research and Development (R&D) approach combined with descriptive research methods. Data were collected from five traditional leaders in Kemiren village, Banyuwangi regency; who maintain sacred traditions such as the Buyut Cili site and the Rebo Wekasan ritual, who were selected as key informants. Data collection instruments included structured interview guides, observation checklists, and documentation tools such as photos and video recordings to capture cultural practices. The results of the study indicate that the concept of the IEK of the Osing tribe can be used in the development of teaching materials in the form of Student Worksheets (LKPD). So that it can be used as an alternative learning resource for high school students in Kemiren Village to better understand their culture and local wisdom.